Ultrasonic sensor concept to fit a ventricular assist device cannula evaluated using geometrically accurate heart phantoms. Issue 5 (7th December 2018) - Dual, Seraina Anne; Zimmermann, Jan Michael; Neuenschwander, Jürg; Cohrs, Nicholas Heinrich; Solowjowa, Natalia; Stark, Wendelin Jan; Meboldt, Mirko; Schmid Daners, Marianne
Abstract: Future left ventricular assist devices (LVADs) are expected to respond to the physiologic need of patients; however, they still lack reliable pressure or volume sensors for feedback control. In the clinic, echocardiography systems are routinely used to measure left ventricular (LV) volume. Until now, echocardiography in this form was never integrated in LVADs due to its computational complexity. The aim of this study was to demonstrate the applicability of a simplified ultrasonic sensor to fit an LVAD cannula and to show the achievable accuracy in vitro. Our approach requires only two ultrasonic transducers because we estimated the LV volume with the LV end‐diastolic diameter commonly used in clinical assessments. In order to optimize the accuracy, we assessed the optimal design parameters considering over 50 orientations of the two ultrasonic transducers. A test bench was equipped with five talcum‐infused silicone heart phantoms, in which the intra‐ventricular surface replicated papillary muscles and trabeculae carnae. The end‐diastolic LV filling volumes of the five heart phantoms ranged from 180 to 480 mL. This reference volume was altered by ±40 mL with a syringe pump. Based on the calibrated measurements acquired by the two ultrasonic transducers, the LV volume was estimated well. However, the accuracies obtained are strongly dependent on the choice of the design parameters. Orientations toward the septum perform better, as they interfere less with the papillary muscles. The optimized design is valid for all hearts. Considering this, the Bland‐Altman analysis reports the LV volume accuracy as a bias of ±10% and limits of agreement of 0%–40% in all but the smallest heart. The simplicity of traditional echocardiography systems was reduced by two orders of magnitude in technical complexity, while achieving a comparable accuracy to 2D echocardiography requiring a calibration of absolute volume only. Hence, our approach exploits the established benefits of echocardiography and makes them applicable as an LV volume sensor for LVADs.